The Influence of Realistic Mathematics Education (RME) Model Based on Ethnomathematics of Engklek Game on Students' Mathematical Problem-Solving Abilities - Selly Madela Br Ginting; Fibri Rakhmawati (IKIP Mataram, 2024)
This research aimed to examine the influence of applying the realistic mathematics education (RME) model based on the ethnomathematics of the Engklek game on students' mathematical problem-solving abilities. The study employed an experimental research design using quantitative methods. The chosen design was a Randomized Two Group Design Posttest Only. Samples were selected using cluster random sampling techniques, resulting in the control class (VII-3) and the experimental class (VII-4). The research utilized lesson plans (RPP), worksheets (LKPD), and a Posttest as the instruments. The data were analyzed using inferential statistical analysis techniques, specifically the Independent Sample T-test with SPSS 25 software. The results of the study indicated that the mean posttest score in the experimental class was 84.76, while the mean posttest score in the control class was 60.90. The hypothesis test at a significance level of 5% yielded a sig.2 tailed value of 0.000. This indicates that the Sig. (2 Tailed) < 0.05, demonstrating a significant effect of applying the realistic mathematics education (RME) model based on the ethnomathematics of the Engklek game on students' mathematical problem-solving abilities. Further research is needed to deepen the understanding of the influence of the RME model based on the ethnomathematics of the Engklek game on students' mathematical problem-solving abilities. Additionally, it is hoped that future researchers can conduct further research using other learning models that are tailored to the subject matter, allowing for a comparison of the obtained mathematical problem-solving abilities. This would enable teachers to select an effective learning model based on the specific needs of their students.